INTEGRATIVE LITERATURE REVIEW: PREVENTION OF NEUROLOGICAL COMPLICATIONS OF HERPES ZOSTER IN ADULTS - ADVANCES, CHALLENGES AND PERSPECTIVES - Ferreira Sampaio, Ruan; Vinicius da Silva Pereira, Marcus; Nayara Coelho Muniz Cardoso, Monique; Soares da Costa, Douglas; Saraiva Sales, Eider; Vinicius Magalhães Guedes, Marcus; Clara Cutrim Lima Sales, Lidia; das Chagas Pimenta Neto, Francisco; Soares da Silva Vilarinho, Gabriely; Joanderson Sousa Costa, Antonio (Health and Society, 2023)
Herpes zoster is a viral disease that can cause neurological complications in adults. In this integrative literature review, 15 scientific articles published in the last five years were analyzed to explore the main topics related to neurological complications of herpes zoster in adults. The topics covered include epidemiology, vaccination, risk factors, treatment, impact on quality of life, and multidisciplinary approach. Herpes zoster has an increased incidence in the elderly and immunocompromised individuals, and is associated with a higher risk of stroke. Vaccination is an effective strategy for preventing the disease and its complications, such as postherpetic neuralgia. Risk factors such as advanced age and severe pain during the acute episode are associated with the development of postherpetic neuralgia. Corticosteroids are an effective treatment option for reducing the risk of this complication. Herpes zoster and postherpetic neuralgia can have a significant impact on patients’ quality of life, especially in the physical and emotional aspects. A multidisciplinary approach involving healthcare professionals from different fields is essential for comprehensive and effective care.